Upaya Guru Pendidikan Agama Islam (PAI) dalam Menumbuhkan Motivasi Pembelajaran PAI Study Multi Situs Di SMKN 1 Boyolangu dan SMKN 1 Bandung Tulungagung - Widiasari, Susi (Jurnal al Hikmah, 2017)
This study in the background backs by a phenomenon that students of Islamic Religious Education (PAI) is less important to them or can say that students underestimate PAI lesson in because these lessons are not included in school subjects in UNAS. This researcher will see how the efforts of teachers of Islamic education in the motivation PAI learning in SMK 1 Bandung Tulungagung.The problem of this thesis is (1) how the efforts of teachers of Islamic religious education in fostering motivation PAI learning at SMK 1 Boyolangu and SMK 1 Bandung Tulungagung (2) How the constraints faced by teachers of Islamic religious education in the motivation of learning PAI in SMKN 1 Boyolangu and SMK 1 Bandung Tulungagung? (3) How Islamic religious education teachers efforts to overcome the obstacles that faced the motivation PAI learning at SMK 1 Boyolangu and SMK 1 Bandung Tulungagung? As for the purpose of this study was to determine the efforts of Islamic religious education teachers in the learning motivation PAI in SMK 1 Boyolangu and SMKN 1 Bandung Tulungagung.This is helpful for the head of SMK 1 Boyolangu, and principals SMK 1 Bandung, as contribute ideas in order to develop and improve the quality of teaching particular subjects of Islamic religious education (PAI), for teachers PAI SMKN 1 Boyolangu and SMKN 1 Bandung is used as the basis of learning PAI , For those readers / other researchers as inputs or significant reference for further research. In this study used observation, interview and documentation. Observation is used to obtain an overview of the efforts of Islamic religious education teachers in terms of motivational PAI learning at SMK 1 Boyolangu and SMKN 1 Bandung Tulungagung were used as research data. While the method used in the documentation and interviews used to explore data about populations, samples, educational facilities and documents SMKN. Efforts will be undertaken to motivate teachers to students is among them through briefings, through awards or riward and by assignment. The constraints faced is that too many students, facilities or infrastructure that is lacking, lack of awareness of the importance of science students of Islamic Education, Islamic Education issues are not at UNAS. And the efforts of teachers to overcome obstacles is sediikit mengerskan voice in the delivery of the lesson, give firmness to the student if crowded, giving advice and pengrahan, embracing students to participate in the motivation in the case of gamma Islamic Education to edify each other